Come back, little Sheba [videorecording (DVD)] - Mann, Daniel, 1912-1991; Lancaster, Burt, 1913-1994; Booth, Shirley; Moore, Terry, 1929-; Jaeckel, Richard, 1926-1997; Inge, William (Paramount DVD collection., 2004)
Lola Delaney is a vulgar, dumpy, less-than-bright "shotgun bride" who is married to recovering alcoholic Doc Delaney. Their unhappy marriage is made even more unhappy when a sexy stranger, Marie, rents a room from Lola. Lola is a tiresome creature who never stops talking, especially about the "imminent" return of her runaway dog Sheba. Doc is having enough trouble staying from the bottle and resigning himself to his marriage without the curvaceous Marie arousing his baser instincts.